Exploring ‘digital placemaking’ - Halegoua, Germaine; Polson, Erika (Convergence (London, England), 2021)
This brief essay introduces the special issue on the topic of ‘digital placemaking’ – a concept describing the use of digital media to create a sense of place for oneself and/or others. As a broad framework that encompasses a variety of practices used to create emotional attachments to place through digital media use, digital placemaking can be examined across a variety of domains. The concept acknowledges that, at its core, a drive to create and control a sense of place is understood as primary to how social actors identify with each other and express their identities and how communities organize to build more meaningful and connected spaces. This idea runs through the articles in the issue, exploring the many ways people use digital media, under varied conditions, to negotiate differential mobilities and become placemakers – practices that may expose or amplify preexisting inequities, exclusions, or erasures in the ways that certain populations experience digital media in place and placemaking.